Interactional and epistemic challenges in students' help-seeking in sessions of mathematical homework support: presenting the problem. Issue 3 (3rd July 2021) - Svahn, Johanna; Bowden, Helen Melander
ABSTRACT: This article concerns students' help-seeking in one particular educational setting in Sweden, namely mathematical homework support. It presents in-depth analyses of video-recorded instances of interactions using multimodal conversation analysis. By exploring how tutors and students with no prior interactional history collaboratively establish an agreement upon what constitutes the student's problem, the study sheds light on the problem presentation and its interactional and epistemic challenges and pitfalls. The results of the study demonstrate the sequential pattern of help-seeking interactions and the crucial role of objects, such as notepads, as epistemic resources for determining the student's problem. It moreover shows how students put their (mis)understandings on display using verbal, embodied and material resources to describe their problem-solving efforts. Finally, it shows how epistemic framings of the help request are of consequence, in which responsibility for the problem presentation may be transferred from student to tutor.